Facile size-controlled synthesis of fucoidan-coated gold nanoparticles and cooperative anticancer effect with doxorubicin. Issue 30 (24th July 2017) - Jang, Hongje; Kang, Kyungtae; El-Sayed, Mostafa A.
Abstract : Facile one-pot synthesis, surface modification and doxorubicin conjugation of anticancer biopolymer fucoidan coated gold nanoparticle enabled highly efficient cancer therapy through cooperative treatment feasibility. Abstract : To conquer cancer, one of the most dangerous and common diseases faced by humanity, many therapeutic approaches have been researched and developed. Discovery of highly effective therapeutic molecules without side effects and novel strategies for their effective delivery are areas receiving recent global interest. Here, we describe a facile one-pot synthetic method for making gold nanoparticles coated with fucoidan, a natural product extracted from brown seaweed and a promising anticancer biopolymer. This nanoparticle formulation with well-controlled size distribution shows promise in enhancing the therapeutic and delivery efficacy. Moreover, stable surface modification of fucoidan coating followed by conjugation of doxorubicin through cleavable linkage significantly improved the anticancer effect. Fucoidan-coated gold nanoparticles containing doxorubicin exhibited more greatly enhanced anticancer effect than any other related platform following fucoidan-based cancer treatment adopting the nanoparticle integrated system.